Comparative trial of seizure recurrence in phenobarbitone maintenance for 72 hrs versus till discharge in moderate to severe perinatal asphyxia in term infants - Koul, Hemangi; Saini, G. S. (International Journal of Contemporary Pediatrics, 2022)
Background: This study was done to look for seizure recurrence in moderate to severe perinatal asphyxia when phenobarbitone was stopped at seizure free interval of 72 hours versus those in whom phenobarbitone was continued upto discharge. Methods: It was a open label randomized trial conducted in neonatal intensive care unit of department of Pediatrics, SMGS from November 2014 to October 2015. This study was conducted on term babies (>37 weeks) with birth asphyxia with moderate to severe encephalopathy according to Levene classification with seizures within 24 hours admitted in NICU. Results: Recurrence of seizures was 6 (10%) in whom phenobarbitone was continued upto discharge and 8 (13.3%) in whom phenobarbitone was stopped after 72 hours of seizure free interval. These results were statistically comparable. Conclusions: There is no beneficial effect of giving phenobarbitone for more than 72 hour in neonates having moderate to severe perinatal asphyxia who are neurologically normal.